Computation and Evaluation of the Electromagnetic Parameters of Amorphous Core Transformers - Thanh, Bao Doan; Quoc, Vuong Dang (Engineering, Technology & Applied Science Research, 2024)
This paper presents an analytical model for computing and designing a three-phase Amorphous Core Transformer (ACT) with a power rating of 3 kVA, 380/127 V. Based on the main parameters obtained from the analytical model, a Finite Element Method (FEM) was developed to simulate the electromagnetic parameters, such as electric currents, operating voltages, and losses. Finally, an ACT installation was carried out with the steel material of code 2605SA1. The simulation results were compared with the experimental measurements under no-load and full-load operating conditions. Furthermore, the no-load loss of ACT was also compared to that of traditional transformers using silicon steel material. The obtained results prove that the use of ACT can save energy in the fields of education, health services, and industries.